Development of Droplet Digital PCR Assay for Detection of Seed-Borne Burkholderia glumae and B. gladioli Causing Bacterial Panicle Blight Disease of Rice - Jiannan Zhang; Jinyan Luo; Lei Chen; Temoor Ahmed; Saqer S. Alotaibi; Yanli Wang; Guochang Sun; Bin Li; Qianli An (Microorganisms, 2022)
Bacterial panicle blight of rice or bacterial grain rot of rice is a worldwide rice disease. Burkholderia glumae and B. gladioli are the causal agents. The early and accurate detection of seed-borne B. glumae and B. gladioli is critical for domestic and international quarantine and effective control of the disease. Here, genomic analyses revealed that B. gladioli contains five phylogroups and the BG1 primer pair designed to target the 3’-end sequence of a gene encoding a Rhs family protein is specific to B. glumae and two phylogroups within B. gladioli. Using the BG1 primer pair, a 138-bp DNA fragment was amplified only from the tested panicle blight pathogens B. glumae and B. gladioli. An EvaGreen droplet digital PCR (dPCR) assay on detection and quantification of the two pathogens was developed from a SYBR Green real-time quantitative PCR (qPCR). The detection limits of the EvaGreen droplet dPCR on the two pathogens were identical at 2 × 103 colony forming units (CFU)∙mL−1 from bacterial suspensions and 2 × 102 CFU∙seed−1 from rice seeds. The EvaGreen droplet dPCR assay showed 10-fold detection sensitivity of the SYBR Green qPCR and could detect a single copy of the target gene in a 20-μL assay. Together, the SYBR Green qPCR assay allows for routine high-throughput detection of the panicle blight pathogens and the EvaGreen droplet dPCR assay provides a high-sensitive and high-accurate diagnostic method for quarantine of the pathogens.